Study of light-meson resonances decaying to 𝐾0s⁢𝐾⁢𝜋 in the B →(𝐾0s𝐾𝜋)K channels - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Physical review, 2025)
A study is presented of 𝐵+ →𝐾0S⁢𝐾−⁢𝜋+⁢𝐾+ and 𝐵+ →𝐾0S⁢𝐾+⁢𝜋−⁢𝐾+ decays based on the analysis of proton-proton collision data collected with the LHCb detector at center-of-mass energies of 7, 8 and 13 TeV, corresponding to an integrated luminosity of 9 fb−1. The 𝐾0S⁢𝐾⁢𝜋 invariant-mass distributions of both 𝐵+ decay modes show, in the 𝑚⁡(𝐾0S⁢𝐾⁢𝜋) <1.85 GeV mass region, large activity which is resolved using an amplitude analysis. A simple model, where 𝐽𝑃⁢𝐶 amplitudes are described by multiple Breit-Wigner functions with appropriate angular distributions, provides a good description of the experimental data. In this approach a complex mixture of 𝐽𝑃⁢𝐶 =0−+, 1 and 1+− amplitudes is observed that is dominated by 𝜂⁡(1405), 𝜂⁡(1470), 𝜂⁡(1760), 𝑓1⁡(1285), 𝑓1⁡(1420) and ℎ1⁡(1405) resonances. The 𝐾0S⁢𝐾⁢𝜋 Dalitz plots are dominated by asymmetric crossing 𝐾*⁢¯𝐾 bands which are different for the two 𝐵+ decay modes. This is due to a different interference pattern between the 1 and 1+− amplitudes in the two channels. Branching fractions are measured for each resonant contribution.
Im Text ist "0" jeweils hochgestellt und "s" jeweils tiefgestellt
LHCb Collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, F.C. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascón, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, S.R. Roy, M. Ruiz Diaz, M. Schiller, M.D. Tat, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und viele weitere]
Gesehen am 11.02.2026